Os manifestos da cultura e resistência face à ocupação colonial na Guiné dita portuguesa 1963-1973 - Gama, Tedse Silva Soares (2022)
The country known today as Guinea-Bissau was part of the former Portuguese colony, It was invaded by Portugal several centuries ago and gained its independence on September 24, 1973 through the National Liberation Struggle. However, It is noticeable that all Guinean citizens carry their attributes due to the value of ethnic belonging, where the same values contributed significantly to the rejection of Portuguese cultural practices, thus, this work whose theme: The manifestations of culture and resistance to colonial occupation in the so-called Portuguese Guinea 1963-1973, aims to understand the processes of resistance and its cultural dynamics in the so-called "Portuguese" Guinea, against the incorporation of Portuguese cultural values in this society, which has a cultural mosaic spread throughout all regions belonging to this territory.